Anger Management in Building Service Quality in Early Childhood Education Institutions - Abd Muhith; Hasan Baharun; Astutik Astutik; Lailatul Mukarromah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research aimed to analyze the application of anger management in improving service quality in early childhood education institutions. The research approach used is a qualitative descriptive approach, case study type. Data collection techniques were carried out through interviews, observation and documentation. Data analysis was carried out in stages, starting from data collection, data presentation, data reduction, and drawing conclusions. The results of the research showed that the application of anger management in improving the quality of services at early childhood education institutions at Namira School II Kindergarten is carried out in a planned and systematic manner, starting from analysis of the internal and external environment, anger management planning to implementation and evaluation. This research had the implication that anger management is able to provide an organizational culture that is conducive to developing the motivation of school residents to do their best for their institution.